1997
DOI: 10.1128/jvi.71.10.7258-7265.1997
|View full text |Cite
|
Sign up to set email alerts
|

The N-terminal region of the luteovirus readthrough domain determines virus binding to Buchnera GroEL and is essential for virus persistence in the aphid

Abstract: Luteoviruses and the luteovirus-like pea enation mosaic virus (PEMV; genus Enamovirus) are transmitted by aphids in a circulative, nonreplicative manner. Acquired virus particles persist for several weeks in the aphid hemolymph, in which a GroEL homolog, produced by the primary endosymbiont of the aphid, is abundantly present. Six subgroup II luteoviruses and PEMV displayed a specific but differential affinity for Escherichia coli GroEL and GroEL homologs isolated from the endosymbiotic bacteria of both vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
63
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 147 publications
(65 citation statements)
references
References 68 publications
1
63
1
Order By: Relevance
“…Point mutations in the RTD impair transport of virions in the gut cells (15) and uptake by the accessory salivary glands (19)(20)(21)(22). Moreover, RTD interacts with GroEL produced by aphid endosymbionts, likely protecting the virus from destruction in the hemolymph (23). The specificity of poleroviruses with respect to their aphid vectors is determined by the N-terminal region of the RTD (18,23) and by its specificity in binding to the GroEL chaperonin of the aphid bacterial symbiont.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Point mutations in the RTD impair transport of virions in the gut cells (15) and uptake by the accessory salivary glands (19)(20)(21)(22). Moreover, RTD interacts with GroEL produced by aphid endosymbionts, likely protecting the virus from destruction in the hemolymph (23). The specificity of poleroviruses with respect to their aphid vectors is determined by the N-terminal region of the RTD (18,23) and by its specificity in binding to the GroEL chaperonin of the aphid bacterial symbiont.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, RTD interacts with GroEL produced by aphid endosymbionts, likely protecting the virus from destruction in the hemolymph (23). The specificity of poleroviruses with respect to their aphid vectors is determined by the N-terminal region of the RTD (18,23) and by its specificity in binding to the GroEL chaperonin of the aphid bacterial symbiont. Despite the preexisting knowledge on polerovirus-aphid interactions, we cannot explain the nontransmissibil- ity of PeWBVYV by aphids.…”
Section: Discussionmentioning
confidence: 99%
“…Buchnera GroEL homologues are found in most aphid taxa and are immunologically closely related. Structural characteristics of Buchnera GroEL are highly similar to those of GroEL of E. coli, and a Ͼ80% sequence identity is present in functionally significant regions (Filichkin et al, 1997;Hogenhout et al, 1998;Ohtaka et al, 1992;van den Heuvel et al, 1994van den Heuvel et al, , 1997. However, unlike E. coli GroEL, Buchnera GroEL is not restricted to the cytosol of the bacteria.…”
Section: Introductionmentioning
confidence: 95%
“…Viruses from the genera Luteovirus, Polerovirus, and Enamovirus display a specific but differential affinity for this protein, which is produced by the primary endosymbiont (a Buchnera sp.) of aphids (van den Heuvel et al, 1994Heuvel et al, , 1997Filichkin et al, 1997). These gram-negative bacteria are harboured in the aphid's haemocoel by specialized polyploid cells, called mycetocytes (Buchner, 1965), and are distantly related to Escherichia coli (Unterman et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Experiments with the nonenveloped plant viruses Luteovirus and Begomovirus revealed that they interact with GroEL, a chaperone of a symbiotic bacterium in aphid vectors (94,95). This interaction is required for circulative transmission and protects against degradation in the vector (96,97). Chaperones are not only involved in protein folding but also in membrane translocation.…”
Section: The Viral Envelope As An Adaptation To Animal Cellsmentioning
confidence: 99%